International Consensus for Provisions of Quality‐Driven Care in Childhood‐Onset Systemic Lupus Erythematosus1. Issue 9 (26th August 2013) - Hollander, Matthew C.; Sage, Jessica M.; Greenler, Alexandria J.; Pendl, Joshua; Avcin, Tadej; Espada, Graciela; Beresford, Michael W.; Henrickson, Michael; Lee, Tsz‐Leung; Punaro, Marilynn; Huggins, Jennifer; Stevens, Anne M.; et al.
<x xml:space="preserve">Abstract</x> Objective To obtain international consensus around processes that support the delivery of high‐quality care to patients with childhood‐onset systemic lupus erythematosus (SLE) based on current recommendations and scientific evidence. Methods To identify process quality indicators (QIs) for the medical care of children and adolescents with childhood‐onset SLE, we sent 2 Delphi questionnaires internationally to 340 physicians who treat these patients. We set consensus at 80% of completed responses. Results Two hundred ninety‐seven physicians (87%) responded to the first Delphi questionnaire and 265 physicians (76%) responded to the second questionnaire. The group achieved consensus for 26 QIs addressing laboratory testing at diagnosis, health maintenance measures, diagnosis and therapy of lupus nephritis, general preventive strategies, surveillance for medication safety, counseling and evaluation of cardiovascular risk factors, as well as transition planning. Of the 26 process QIs for use in childhood‐onset SLE, 11 matched those established for adults with SLE, 9 required modification, and consensus was reached for an additional 6 QIs specific to children. Conclusion An international consensus for a set of process QIs for childhood‐onset SLE was reached that considers unique aspects of children with childhood‐onset SLE. The presented set of QIs for children and adolescents with childhood‐onset SLE defines agreed‐upon standards of medical care.